Efektivitas Kombinasi Massage dan Passive Stretching terhadap DOMS dan Fleksibilitas Otot Hamstring - Yohan Adi Satria; Setya Rahayu; Sandhya Kresnajati; Riki Edo Saputro (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study examined whether massage and passive stretching reduced Delayed Onset Muscle Soreness (DOMS) and improved hamstring flexibility in Klinik Utama Satu Sehat Semarang patients. A quasi-experimental one-group pretest–posttest approach was employed with 20 purposively selected individuals. The VAS rated DOMS intensity and the Sit and Reach Test tested flexibility. The data was analysed using the Shapiro-Wilk test and paired sample t-test (α = 0.05). There was a substantial decrease in DOMS severity from 6.12 to 2.85 (p < 0.05) and an increase in hamstring flexibility from 23.40 to 30.60 cm (p < 0.05). Conclusion: Massage and passive stretching alleviate DOMS and increase hamstring flexibility.